Probable impossibilities : musings on beginnings and endings - Lightman, Alan P., 1948- (Pantheon Books, 2021)
"Before the discovery of quarks, we hadn't imagined anything smaller than protons and neutrons. Are quarks the end of the line, the smallest imaginable objects in nature? Can the universe be divided into infinitely smaller units in the same way the universe is ever-expanding? Alan Lightman explores these questions in his characteristic accessible and lyrical prose, considering the igniting element behind consciousness, the origin of life, the anatomy of a smile, our fickle memories. Probable Impossibilities brings together recently published and four original essays. Throughout, Lightman guides a discussion on what we know of the universe, life, the mind, and the conception of things vastly larger than ourselves in time and space"--